1p-Enh-regulated CYP4B1 alleviates NNK-induced heart failure and lung cancer via the STAT3 pathway - Li Dai; Jun Hu; Ye Yang; Bingjun Qian; Xianglin Zuo (PLoS ONE, 2025)
Heart failure (HF) and lung cancer (LC) often coexist, yet their shared molecular mechanisms are unclear. We analyzed transcriptome data from the NCBI Gene Expression Omnibus (GEO) database (GSE141910, GSE57338) to identify 346 HF‑related differentially expressed genes (DEGs), then combined weighted gene co-expression network analysis (WGCNA) pinpointed 70 hub candidates. Further screening of these 70 hub candidates in TCGA lung cancer cohorts via LASSO, Random Forest, and multivariate Cox regression suggested CYP4B1 as the only independent prognostic marker. Subsequent ROC analysis validated CYP4B1’s diagnostic power in both HF and LC (AUC > 0.80). Immune-cell infiltration analysis demonstrated that high CYP4B1 expression correlated with increased infiltration of M2 macrophages. Experiments revealed CYP4B1 downregulation in angiotensin II (Ang II)-induced cardiomyocytes (AC-16) and LC cells (A549 & H1703). CYP4B1 overexpression attenuated angiotensin-II–induced cardiac hypertrophy and inhibited the migration, invasion, and proliferation of LC cells. Mechanistic studies revealed that CYP4B1 suppresses the JAK-STAT3 signaling, and we identified a novel distal enhancer, 1p‑Enh, that regulates CYP4B1 expression via chromatin looping. Additionally, prolonged exposure to the tobacco carcinogen NNK suppressed 1p‑Enh activity and downregulated CYP4B1 expression. These findings demonstrate the critical role of the NNK‑induced 1p‑Enh/CYP4B1 regulatory axis in both HF and LC, suggesting that CYP4B1 may serve as a potential therapeutic target for the concurrent treatment of HF and LC.